2005
DOI: 10.1093/aob/mci177
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Petunia sensu Jussieu (Solanaceae) using Chloroplast DNA RFLP

Abstract: The separation of Petunia sensu Wijsman and Calibrachoa was supported by chloroplast DNA analysis. Two groups in the Calibrachoa were also recognized with a high degree of confidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 26 publications
4
45
0
3
Order By: Relevance
“…We have selected the solanaceous genus Petunia (2n ¼ 14) for our studies on the genetics of pollination syndromes. Petunia is native to South America and has been divided into up to 16 species, but the phylogeny of the genus has not yet been rigorously resolved (Ando et al 2005;Kulcheski et al 2006;Lorenz-Lemke et al 2006, Stehmann et al 2009). Most members of the genus present characteristics of beepollinated species (typical representatives: P. integrifolia or P. inflata).…”
Section: Introductionmentioning
confidence: 99%
“…We have selected the solanaceous genus Petunia (2n ¼ 14) for our studies on the genetics of pollination syndromes. Petunia is native to South America and has been divided into up to 16 species, but the phylogeny of the genus has not yet been rigorously resolved (Ando et al 2005;Kulcheski et al 2006;Lorenz-Lemke et al 2006, Stehmann et al 2009). Most members of the genus present characteristics of beepollinated species (typical representatives: P. integrifolia or P. inflata).…”
Section: Introductionmentioning
confidence: 99%
“…integrifolia under the latter taxa, justifying this choice with the association of several characteristics to the different environments where these plants grow. Previous evolutionary approaches (Longo et al , 2014; Reck-Kortmann et al , 2014; Ramos-Fregonezi et al , 2015) have supported the suggestions of Stehmann and Bohs (2007) and Stehmann et al (2009), but the genetic variation found in WOX genes reinforces the proposition of Ando et al (2005a,b), this indicating the need for more studies including these different morphologies.…”
Section: Discussionmentioning
confidence: 58%
“…Petunia bajeensis , a species that occurs just in lowlands, was the sister group of the highland species (Figure 1B), confirming previous findings of phylogenies based on combined nuclear and plastid markers (Reck-Kortmann et al , 2014). However, such relationships were not observed in phylogenies obtained through plastid sequence analysis (Lorenz-Lemke et al , 2010) or plastid RFLP (Ando et al , 2005a), in which P. bajeensis is placed in the lowland group of species, or those based only on nuclear sequences (Chen et al , 2007; Kriedt et al , 2014), in which P. bajeensis is placed in the highland group, with different sister species. All highland species share morphological traits with P. bajeensis , especially the stamen filaments adnated up to half of the corolla tube (Stehmann et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aunque Ando et al (2005) citan mecanismos de aislamiento genético en el género Petunia sensu Jussieu, en especial para la rama monofilética de C. parviflora, la certeza de los resultados necesita aún de posteriores estudios.…”
Section: Análisis De Correlación Entre La Variable Original Del Compounclassified